Granisetron, Kombinasi Metoklopramid dan Deksametason Terhadap Mual Muntah Paska Laparatomi - I Nyoman Panji; Heru Dwi Jatmiko; Aria Dian Primatika (JAI (Jurnal Anestesiologi Indonesia), 2010)
Backgroud: Post-operative Nausea and Vomitus (PONV) is commonly unsatisfy experienced by patient after surgical procedures with general anesthesia. Laparatomy is one among high risk groups for PONV.Objective: The aim of this study to compare the efficacy between granisetron 1 mg and combination metoclopramide 10 mg and dexamethasone 8 mg in preventing PONV after laparatomy.Methods: This research was a clinical trial stage 1 in 48 patients undergoing laparatomy surgery by general anesthesia. All patients were observe the 6 hours fasting period before induction of anesthesia. Patient randomly divided in to two group. Group I treatme nt with granisetron that given 30 to 60 minutes before end operation. Group II treatment with metoclopramide 10 mg and dexamethasone 8 mg, that dexamethasone given before induction of anesthesia and metoclopramide administration 30 to 60 minutes before end operation. All patient were observe the nausea and vomiting 24 hours post operative.Results: There was no significant difference for patient characterictics data distribution between two group before treatment. There was no significant difference to decr ease nausea and vomiting after laparatomy between two groups. Patient who had received intravenous 1 mg granisetron incidence nausea-vomiting was 83,3 % while patient who had received the combination 10 mg metoklopramid and 8 mg dexamethasone incidence nau sea—vomiting was 75%.Conclusion: There was no antiemetics which fully effective to exceed post operative nausea and vomitus. Combination 10 mg metoclopramide and 8 mg dexamethasone has similar effect like 1 mg granisetron on prevent Post -operative Nausea and Vomitus but higher adverse effects.Keywords : nausea, vomiting, granisetron, metoclopramide, dexamethasone, laparatomyABSTRAKTujuan: Penelitian ini bertujuan untuk membandingkan efektifitas antara granisetron 1 mg dan kombinasi metoklopramid 10 mg dengan deksametason 8 mg dalam mencegah mual muntah paska laparatomi. Metode: Penelitian ini merupakan penelitian tahap I pada 48 penderita yang menjalani laparatomi dengan anestesi umum. Semua penderita dipuasakan 6 jam sebelum dilakukan induksi anestesi. Pasien secara random dibagi menjadi dua kelompok. Kelompok I diberikan granisetron 30 sampai 60 menit sebelum operasi selesai. Dan kelompok II diberikan deksametason sebelum induksi anestesi dan metoklopramid 30 sampai 60 menit sebelum operasi selesai. Semua pasien diamati kejadian mual muntah paska operasi selama 24 jam.Hasil: Didapatkan perbedaan tidak bermakna pada distribusi karakteristik pasien antara kedua kelompok sebelum perlakuan. Hasil uji statistik menunjukkan terdapat perbedaan yang tidak bermakna kejadian mual muntah paska laparatomi pada kedua kelompok. Dimana pasien yang diberikan granisetron 1 mg didapatkan kejadian mual muntah sebesar 83,3 % sedangkan pasien yang diberikan kombinasi metoklopramid 10 mg + deksametason 8 mg didapatkan angka kejadian mual muntah sebesar 75%.Simpulan: Tidak ada antiemetik yang mampu sepenuhnya mencegah mual muntah paska operasi. Pemberian kombinasi metoklopramid 10 mg + deksametason 8 mg mampu mengurangi resiko mual muntah paska operasi yang hampir sama efektifnya dengan granisetron 1 mg dengan efek samping lebih banyak.Kata kunci : mual, muntah, granisetron, metoklopramid, deksametason, laparatomi